2016
DOI: 10.3390/s16030313
|View full text |Cite
|
Sign up to set email alerts
|

Radiometric Calibration of a Dual-Wavelength, Full-Waveform Terrestrial Lidar

Abstract: Radiometric calibration of the Dual-Wavelength Echidna® Lidar (DWEL), a full-waveform terrestrial laser scanner with two simultaneously-pulsing infrared lasers at 1064 nm and 1548 nm, provides accurate dual-wavelength apparent reflectance (ρapp), a physically-defined value that is related to the radiative and structural characteristics of scanned targets and independent of range and instrument optics and electronics. The errors of ρapp are 8.1% for 1064 nm and 6.4% for 1548 nm. A sensitivity analysis shows tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 60 publications
0
14
0
Order By: Relevance
“…Therefore, independent calibration of instruments is recommended, utilizing objects with equivalent geometry and reflective properties to those found in the ecosystem to be sampled. Fortunately, pulse-level uncertainties can be robustly established with everimproving methods (Kaasalainen et al 2009;Li et al 2016).…”
Section: Evaluation Of the Microstate Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, independent calibration of instruments is recommended, utilizing objects with equivalent geometry and reflective properties to those found in the ecosystem to be sampled. Fortunately, pulse-level uncertainties can be robustly established with everimproving methods (Kaasalainen et al 2009;Li et al 2016).…”
Section: Evaluation Of the Microstate Modelmentioning
confidence: 99%
“…; Li et al. ) and the SALford Advanced Canopy Analyzer (SALCA) (Danson et al. ), and commercially available instruments such as the Riegl VZ‐400 (Calders et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with ALS data, only a few recent studies have focused on the TLS intensity correction. And its correction also faces more unique challenges than ALS data (Li et al, 2016). Many studies have found that the intensity data does not follow the LiDAR equation in the near range and different TLS systems may result in different intensity-range relations (Kaasalainen et al, 2011;Fang et al, 2014;.…”
Section: Intensity Data Correctionmentioning
confidence: 99%
“…However, using intensity information from a single wavelength scanner limits this separation because the received intensity is a function of the spectral reflectance properties of the canopy constituents, the area of the beam that is intercepted, and the local angle of incidence [37]. The dual-wavelength scanners DWEL and SALCA try to overcome the limitations of a single-wavelength scanner by taking the spectral ratio of the two laser wavelengths at approximately 1064 and 1550 nm [37], [38].…”
Section: Evaluation Of the Radiometric Calibrationmentioning
confidence: 99%